(untitled) (INNOTEC, 2017)
Stable carbon and nitrogen isotope composition of plants, sediments and animals has been used as a common tool employed in different studies including ecology, and paleoenvironmental reconstruction. Because of the different isotopic values among primary producers, this is a powerful tool to trace pathways of exchange of organic matter between ecosystems. We describe the basic principles, including nomenclature, of the application the isotopic approach in coastal environmental studies. Furthermore, we present three recent studies with the isotopic approach for: 1) assess the distribution of deposited organic matter within the Río de la Plata estuary, 2) determine the trophic importance of a diatom from a surf zone in sandy beach food webs, and 3) assess the influence of the anthropogenic organic matter within the Montevideo Bay. The isotopic composition of organic matter sources allowed the study of different aspect of ecosystem function including the characterization of the organic matter pathways. This review highlighted the significant utility of this complementary tool for the study of ecological process and could be useful in the identification of changes in coastal environments.